NURSING INTERVENTIONS AIMED AT QUITTING SMOKING - Mona Mohammed Alanazi, Areej Massad Alnufai, Alotaibi, Meshal Mohammed, Fahad Makki Mahworry, Mohammed Abdullah Hussien Alnodali, Tariq Ebrahim Alhumaid, Khaled Ali Alshahrani, Mohammed Ahmed Karshami, ,; Fatimah Mohammed Abutalib, Samah Awad Almobarak, Amal Faraj Algamdi, Najwa Awad Almubark, Saleh Abdullah Aldukhail,Mohammed Nasser Alotaibi, Mohammed Mutlaq Althobaiti, (Chelonian Research Foundation, 2022)
This review examines the effectiveness of nursing interventions in helping adults quit smoking. Forty-two trials met the inclusion criteria, with interventions delivered by nurses to adult smokers in various healthcare settings. The analysis focused on nurse-provided advice, counseling, and strategies to support smoking cessation. The review found that nursing interventions can increase quit rates compared to usual care. Pooled data from studies showed a 28% increase in quit rates at follow-up for those receiving a nursing intervention. High-intensity interventions, involving more frequent contact and support from nurses, did not show a statistically significant advantage over low-intensity interventions. Interventions delivered as part of cardiac rehabilitation programs yielded the most promising results. Keywords: smoking cessation, nursing interventions, adult smokers, quit rates.